Saint young men. 3 - Nakamura, Hikaru, 1984- (Kodansha Comics, 2020)
"Buddha the Enlightened One and Jesus, Son of God, have successfully brought the 20th century to a close, and after a few millennia of guiding humanity to salvation, these two sacred ones are in need of some rest and relaxation. They decide to share an apartment on Earth in Tokyo, but living among mortals in the 21st century is no cakewalk for the saintly duo ... The sagely saga continues as Buddha and Jesus's punny romp through Tokyo twists and turns in new directions. there are no shortages of sacros-antics as the pair and their heavenly retinue venture to Japanese tourist landmarks like Tokyo Tower, play their saintly sports, and continue to refine their comedy act - all while learning new lessons about the mundane tasks of daily life in Japan."--Provided by publisher.